The adversative conector “mas”: semantic nuances and discursive intentionality in scientific articles - Santos, David Ruan Bezerra; Santos, Aymmée Silveira (Entrepalavras, 2025)
Understanding and elaborating any textual/discursive genre foresees the need for conscious use of the structures available in our language. One of the genres that circulates the most in the academic environment is the scientific article, whose main purpose is to disclose research from an investigation. In this sense, this article aims to analyze the semantic shades of the adversative connector “mas” in scientific articles, highlighting their relationship with the discursive intentionality of users responsible for the textual elaboration in argumentative construction. Thus, the specific objectives are unfolded: a) identify and describe semantic shades of the adversative connector “mas” in scientific articles; b) Investigate how the uses of the adversative connector “mas” reflect the textual and discursive organization for the realization of the authors' communicative purposes. For this, a research of a qualitative, exploratory, descriptive and analytical nature was conducted, having as theoretical background studies developed by Castilho (2014), Neves (2011), Koch and Elias (2016), Marcuschi (2008), Koch and Travaglia (2001), Antunes (2009; 2010), among others. It was found that the "mas" is used as a linguistic-discursive mechanism that directs and reinforces the argumentative construction, realizing the author's intentionality in scientific articles. It becomes crucial for the development of academic literacy to understand the different argumentative structures and the strategies necessary to ensure cohesion, organization and textual-discursive intentionality in productions of dissemination of scientific knowledge.